Phosphorus puts a mortgage on restoration of species‐rich grasslands on former agricultural land. Issue 4 (13th January 2022) - Goossens, Elias P.; De Schrijver, An; Schelfhout, Stephanie; Vanhellemont, Margot; Verheyen, Kris; Mertens, Jan
Abstract : Large‐scale biodiversity loss is one of the most urgent global issues. The Convention on Biological Diversity created a vision to ecologically restore ecosystems by 2050. The European Union follows this ambition, and member states are required to select Special Areas of Conservation (SACs) to develop and restore; one example is species‐rich semi‐natural grassland. Species‐rich grassland restoration requires time for restoring both abiotic conditions, e.g. low soil phosphorus concentrations, and biotic conditions, e.g. introduction of missing species. For 507 grasslands (in northern Belgium) situated in SACs, we calculated the time needed for restoring necessary phosphorus‐poor conditions. Only 11% of the grasslands already met the strictest phosphorus‐target. We found that less than a fourth of the other 452 grasslands will reach this phosphorus‐target by 2050 through mowing. P‐mining, a more intensive technique involving fertilization of nitrogen and potassium, could help achieve this phosphorus‐target on about slightly more than a third of these grasslands by 2050. The soil iron concentration strongly affected the restoration times. A total of 65% of the grasslands will require alternatives like topsoil removal or selection of a different, less ambitious grassland target. These calculations do not include the time needed for biotic restoration. Because grassland restoration is a long‐term process, we advocate better protection of still existing species‐rich grasslands. Restoration is a last resort in safe‐guarding biodiversity.